Exploring the Intersection of Philanthropy, Research, and Scholarship in a Third World Context - Koirala-Azad, Shabnam (Social justice, 2009)
The article presents research on the conditions of higher education in Nepal and related brain drain effects through the method of a transnational participatory action research (PAR) project. The research offers a qualitative description of Nepali higher education and the inequalities present, and it also presents an inquiry into the Nepali immigrant community in the U.S. and the brain drain concept. The author discusses the challenges of the research in a Third World context such as issues of prejudice, power, and legitimacy and offers methods and strategies to improve further research.